Dentigerous Cyst in the Maxillary Anterior Region of a Pediatric Patient - Nagarajan, Nivethitha; Jayachandran, Sadaksharam; Jayaram, Vidya; Nisha, Aarthi (Annals of the National Academy of Medical Sciences (India), 2020)
Dentigerous cyst is a common type of odontogenic cyst of the oral and maxillofacial region. It commonly occurs in the second or third decades and rare cases appear in the first decade of age. It is a developmental cyst associated with unerupted/impacted tooth. Radiographically, it appears as unilocular, radiolucent area along the cementoenamel junction of the associated tooth. Larger dentigerous cysts may be treated with marsupialization, and smaller dentigerous cysts are treated with enucleation of the cyst and extraction of the associated tooth. This case report presents a case of dentigerous cyst in the right maxillary region in a young child and was diagnosed using radiographs and removed by surgical excision.
Keywords: dentigerous cyst; enucleation; maxilla; radiolucent; squamous epithelium; unerupted tooth